High resolution study on planktonic foraminifera across the Paleocene-Eocene thermal maximum in the expanded Tethyan Forada section ( Italy): paleoecological and paleoenvironmental implications - LUCIANI, Valeria; Agnini C.; Fornaciari E.; Giusberti L.; Backman J.; Rio D. (European Geosciences Union, 2007)
(---)